Fungsi Pembacaan Sab’u Al-Munjiyât Bagi Komunitas Pesantren Putri Al-Mahrusiyah - Kholila Mukaromah; Dewi Aulia; Khaerul Umam (Institut Agama Islam Negeri (IAIN) Keiri, 2022)
This article aims to reveal the function of the practice of reciting sab'u al-munjiyat in the female Islamic boarding school al-Mahrusiyah. Kediri. In their daily life, the students are required to take part in the reading of sab'u al-munjiya>t after the congregational maghrib prayer. Sab'u al- munjiya>t is a collection of seven selected suras, namely as-Sajdah, Yasin, ad-Dukhon, al-Waqi'ah, al-Mulk, al-Insan, and al-Buruj. Each of the seven surahs is read one sura in one day according to the existing schedule. There are two focuses of study in this research: 1) how is the practice of reading sab'u al- munjiya>t at Pesantren Putri Al-Mahrusiyah?, and how is the function of reading sab'u al-munjiya>t based on the structural functional paradigm of AR Redcliffe Brown? . This research includes field research and is studied using qualitative research methods. Data collection was obtained through interviews, observations, and documentation studies. Furthermore, data analysis was carried out using the AR. Redcliffe-Brown structural functional paradigm. The results of this study indicate; First, the practice of reading sab'u al-munjiyat is carried out by following several sequences. These include performing ablution, arranging prayer rows, performing prayers, praying Maghrib in congregation, reading some of wirid, and reading sab'u al- munjiya>t. 2) There are two structures in the practice of reading sab'u al- munjiya>t, namely the subject structure and the structure of reading sab'u al- munjiya>t. The subject structure consists of two social structures, namely kyai and santri. Meanwhile, in the structure of reading sab'u al- munjiya>t there are two network components, namely the structure of the form and the structure of the wirid. In terms of function, the practice of reading sab'u al- munjiya>t has many functions that cannot be separated from the basic needs of the entire network in its social structure. These functions include religious functions, educational functions, social functions, and sectarian ideological functions.